Multimedia identities: an analysis of How Tasty Was My Little Frenchman. (11th March 2019) - Nagib, Lúcia
Abstract: This essay draws on tropicalist intermediality as a means to gain a deeper insight into the political contribution made by the film How Tasty Was My Little Frenchman, directed in 1970 by Cinema Novo exponent, Nelson Pereira dos Santos, and first screened in 1971. I argue that, beyond the film's sensational focus on cannibalism, its intermedial relations, under the influence of Tropicalism, bring about a new dimension of hybridity and transnationalism hitherto absent from the Cinema Novo agenda. How Tasty Was My Little Frenchman presents a distinctive multiperspectival structure derived from the self-revealing and self-standing form in which its raw materials are shown. For example, Hans Staden's book was not only a source for the fictional plot, but actual chunks of its text are displayed, alongside sixteenth-century drawings, letters, poems, decrees and testimonials by French and Portuguese colonizers, in the form of title cards or voiceover commentary, often in contradiction with the images and between themselves, thus multiplying the narrative layers that preserve their own, original semantic agency. This Tropicália-inspired multimedia procedure not only disregards the attachment to medium specificity that had hitherto characterized political cinema in Brazil, but also deconstructs the unified figure of the auteur, held as the supreme creator in the early Cinema Novo days. I examine the possible political utopia contained in the film's hybrid form, which opens up to a supranational view of the world in which humans, whatever their origin or standing, become mere vessels of their cultural capital.